2021
DOI: 10.3390/ijms22083872
|View full text |Cite
|
Sign up to set email alerts
|

The Zinc-Sensing Receptor GPR39 in Physiology and as a Pharmacological Target

Abstract: The G-protein coupled receptor GPR39 is abundantly expressed in various tissues and can be activated by changes in extracellular Zn2+ in physiological concentrations. Previously, genetically modified rodent models have been able to shed some light on the physiological functions of GPR39, and more recently the utilization of novel synthetic agonists has led to the unraveling of several new functions in the variety of tissues GPR39 is expressed. Indeed, GPR39 seems to be involved in many important metabolic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 172 publications
0
36
0
Order By: Relevance
“…Noteworthy is the fact that we verified using GPR39 KO mice that GPR39 is a target for TC-G 1008 in this model. As one of the first pharmacological tool compounds for GPR39, TC-G 1008 has been used extensively to characterize the function of the receptor [13] but no study up to date has demonstrated in vivo that the effects of TC-G 1008 are mediated by GPR39. The compound was initially described as selective for GPR39 [21], but a further study suggested that it is a specific one as it may also bind to the serotonin 5HT1A receptor [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noteworthy is the fact that we verified using GPR39 KO mice that GPR39 is a target for TC-G 1008 in this model. As one of the first pharmacological tool compounds for GPR39, TC-G 1008 has been used extensively to characterize the function of the receptor [13] but no study up to date has demonstrated in vivo that the effects of TC-G 1008 are mediated by GPR39. The compound was initially described as selective for GPR39 [21], but a further study suggested that it is a specific one as it may also bind to the serotonin 5HT1A receptor [22].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, extracellular zinc was suggested to activate a G-protein-coupled receptor (GPCR), namely GPR39 [9,10]. The existence of a GPCR activated by zinc ions was postulated before [11] although there is still debate whether the physiological/ pathophysiological concentrations of zinc are sufficient to activate the receptor [12] and whether zinc is the only one agonist [13].…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitory effects on NF-kB activation have been discussed as a decisive mechanism underlying the anti-inflammatory effects of zinc [48]. The anti-calcific effects of zinc are at least partly mediated by GPR39, a G protein-coupled receptor that is activated by extracellular zinc and widely associated with anti-inflammatory effects [49]. The activation of GPR39 has been associated with reduced monocyte-to-endothelial adhesion [50] and reduced cardiovascular calcification [21,23].…”
Section: Discussionmentioning
confidence: 99%
“…Such feedback mechanisms may protect cells from excitotoxicity through GPR39. For the remainder of this review, we will focus on GPR39’s roles in the CNS; for a comprehensive review of GPR39 pharmacology, please refer to Laitakari and colleagues’ excellent article [ 68 ] in a prior issue of this journal.…”
Section: Deorphaned Endogenous Ligands Implicate Gpr39 In Moderating Neuro-excitability and Vascular Tone Through Gαq And/or Gαs Pathwaysmentioning
confidence: 99%
“…GPR39-C3 is orally bioavailable and has been evaluated as a treatment for type 2 diabetes through its ability to increase GLP-1 (glucagon-like peptide 1) [66]. Some synthetic agonists (LY2784544 and GSK2636771) have been evaluated in animal models, with ongoing human trials in myeloproliferative disorders and cancers ( [65,68]; www.clinicaltrials.gov available on 30 July 2021; GPR39-C3 has also been investigated for its antidepressant potential in animals [61].…”
Section: Synthetic Ligands Biased Agonism and Receptor Desensitizationmentioning
confidence: 99%